The Relationship Between Iron-Rich Food Consumption and Iron Supplement Adherence with the Incidence of Anemia among Adolescent - Khoirunnisa, Nisa; Nurhartanto, Adhi; Astuti, Dewi Woro (Genius Journal, 2026)
Introduction: Anemia remains a significant public health problem among adolescents, particularly female students, and is commonly associated with inadequate iron intake and low hemoglobin levels, which can negatively affect physical performance and cognitive function. Patterns of iron-rich food consumption and adherence to iron supplement intake are considered key factors influencing the occurrence of anemia among students, yet these behaviors are often suboptimal and require further investigation. Objective: Anemia is the result of examining hemoglobin (Hb) levels in the blood that are lower than normal and this condition can be caused by a lower number of red blood cells. The purpose of this study was to determine the relationship between food consumption patterns of iron sources and compliance with the consumption of blood supplement tablets with the incidence of anemia in grade XI students at MAN 1 Lampung Utara. Method: This type of research is quantitative, employing an analytic research design, specifically a cross-sectional design. The population in this study were all grade XI students at MAN 1 Lampung Utara with a total of 149 students. The sampling technique used a proportionate stratified random sampling method with a total sample of 65 respondents. Result: The results of this study are the relationship between the pattern of consumption of iron-source foods with anemia characterized by the results of a p-value of 0.001 and the relationship between compliance with consumption of blood supplement tablets with anemia characterized by the results of a p-value of 0.022. Conclusion: It is hoped that female students can change the frequency of food consumption patterns, especially those containing iron, and routinely consume blood supplement tablets according to their recommendations in order to fulfill and increase iron reserve storage in the body in order to prevent anemia.